Effect of graphitization and activation on vegetable oil-derived carbon soot nanostructures for Zinc Ion hybrid capacitors - Pandey A.; Maurya P.K.; Mishra A.K. (My University, 2025)
Hybrid Capacitors can provide solutions for fast and efficient energy supply. Here, we demonstrate oil-derived porous carbon soot nanostructures (pristine, activated, and graphitized) used as novel cathode materials for Zinc-ion hybrid capacitors (ZIHCs) with aqueous and solid electrolytes. The graphitized carbon soot (GCS) based aqueous ZIHC shows maximum discharge capacitances 255 F g−1 at 0.2 A g−1 with a maximum energy density of 90.8 W h kg−1 at power density of 160.23 W kg−1 and maximum power density of 8338.2 W kg−1 at energy density of 32 W h kg−1 within the voltage range of 0.2–1.8 V. The GCS-based aqueous ZIHC provides exceptional stability with a high-capacity retention of 95 % and nearly 100 % of coulombic efficiency up to 10,000 cycles. Moreover, solid-state zinc ion hybrid capacitors (SZIHCs) are developed by utilizing a durable polyvinyl alcohol (PVA) hydrogel with zinc sulphate as the solid-state electrolyte, achieving a high discharge capacitance of 480 F g−1 (Specific capacity = 219.7 mA h g−1) at a current density of 1 A g−1. The GCS- based SZIHC demonstrates an impressive energy density of 173.7 W h kg−1 at 799.8 W kg−1 power density coupled with a notably higher power density of 16000 W kg−1 at energy density of 21.6 W h kg−1, while maintaining outstanding nearly 98 % capacitance retention and 100 % coulombic efficiency over 10,000 cycles. © Elsevier Ltd